Influence of glucose and stirring in the fermentation process in order to produce anti- Candida metabolites produced by Streptomyces sp. - Silvia Katrine Silva Escher; José Jeosafá Vieira de Sousa Júnior; Adrielle Leal Dias; Elba Lúcia Cavalcanti de Amorim; Janete Magalí de Araújo
ABSTRACT This study evaluated the influence of glucose and stirring in the fermentation process in order to produce anti-Candida metabolites produced by Streptomyces sp. MPO4 isolated from Amazon soil. The anti-Candida metabolites production was registered after 24 h of fermentation in stirred ISP2 medium, having antifungal inhibition halos between 12.3 mm and 25.3 mm, yielding higher production of anti-Candida agents after 96 h. Stirring was a determining factor for the production of anti-Candida secondary metabolites, since the absence of glucose reflected in the late production of the antifungal starting from Streptomyces sp.